Food and nutrition security strategy for Guyana (Guyana. Ministry of Agriculture GeorgetownGY, 2011)
Presents a food and nutrition security strategy which aims to facilitate sustainable and stable employment-generating opportunities; to promote systems to enable the use and consumption of healty foods; and to promote increased institutional coordination and functioning for improved fodd and nutrition security.
Keywords: FOOD POLICY